VARIATION OF THE POTASSIUM-SODIUM RATIO IN WATERS OF THE RAZDOL'NAYA ESTUARY AND AMUR BAY - Tishchenko P.Y.; Anikiyev V.V.; Il'ichev V.I. (My University, 1987)
The distribution of the macrocomponents of sea water is governed primarily by salinity. But several investigators have found a variation in the cation-chloride ratios, ranging from 1 to several percent (see, e.g., [1-8]). The reasons for this variability are in many respects unclear. This prompted the authors to study the distribution of such conservative elements as sodium and potassium in the estuary of the Razdol'naya River and in Amur Bay. Experimental findings indicate that the absolute deviations between conservative behavior of potassium and the measured values were about 10-5 mol/kg for nearly all points. The concentration of suspended matter in this mixing zone was 35 mg/liter. If the suspended matter is in ion-exchange equilibrium and the flows of suspended matter and river water are equal in this mixing zone, then the ion exchange capacity of the suspended matter for potassium will be 30 meq/100 g.